Addition of Eco Enzyme as a Biostimulant for Liquid Organic Fertilizer for the Growth of Curly Lettuce (Lactuca sativa L.) in the Kampoeng Pintar Oase Tembok Gede Vertical Garden - Mulyono, Azzahra Imairel Putri Diyati; Fitrihidajati, Herlina; Candra, Adi; Nurcholis, Nurcholis; Aseyan, Aseyan (Universitas Muhammadiyah Malang, 2026)
The use of liquid organic fertilizer (LOF) from garlic and onion skin waste has the potential to be an environmentally friendly alternative to chemical fertilizer AB Mix in the cultivation of curly lettuce (Lactuca sativa L.) in a vertical garden system. This research aims to describe the quality of LOF with the addition of Eco Enzyme, analyze the effect of various LOF concentrations on the height, number, biomass, and morphology of curly lettuce, and describe the impact of implementing LOF application that can support SDG 2.2 food security indicators. The research was conducted from September to November 2025 at the Oase Tembok Gede Smart Village in Surabaya. The research method uses 2 stages: LOF prototype creation and nutrient content testing at BSPJI Surabaya, referring to the Minister of Agriculture Decree No. 261/KPTS/SR.310/M/4/2019. Additionally, LOF implementation on curly lettuce plants in a vertical garden with parameters of height, number, biomass, and morphology of curly lettuce. The data analysis technique used was descriptive quantitative analysis, followed by a Completely Randomized Design (CRD) with four treatments (P0: budikdamber water control, P1: 40 mL, P2: 50 mL, P3: 60 mL) and three replications. The quality test results showed a K₂O content of 2.03% meeting the minimum standards of the Ministry of Agriculture Decree No. 261/KPTS/SR.310/M/4/2019. ANOVA analysis showed no significant difference between treatments (p > 0.05), but treatment P3 (60 ml) produced the best growth with a height of 11 cm, 7 leaves, a fresh weight of 11 grams, and fresh green leaves. Although the nutrient quality of LOF is not yet optimal, the growth of curly lettuce remains good because it is supported by suitable environmental conditions. This research supports SDG indicator 2.2 (Zero Hunger) thru the utilization of household waste for local food security based on urban agriculture.